Implementasi Simulasi ERP Odoo sebagai Upaya Membangun Job-ready skills pada Siswa Kompetensi Keahlian Akuntansi kelas XII SMK PGRI 3 Bogor - Amelia Oktrivina; Yetty Murni; Salis Musta ‘Ani; Shanti Lysandra; Sailendra Sailendra; Agung Terminanto; Amanda Putri Alisha; Putri Rizki Samsumantri (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2026)
The increasing adoption of digital technology in industry requires vocational graduates to possess competencies in integrated information systems, including Enterprise Resource Planning (ERP). However, accounting students generally have limited exposure to ERP applications during the learning process. This community service program aimed to improve the job-ready skills of twelfth-grade Accounting students at SMK PGRI 3 Bogor through ERP Odoo simulation. The program involved 31 students and was conducted using participatory training consisting of lectures, demonstrations, hands-on practice, discussions, and evaluations through pre-test and post-test. The training covered ERP concepts, business process integration, and the use of the accounting module in ERP Odoo. The evaluation results indicated an improvement in students' understanding of ERP concepts, supported by higher post-test scores and positive participant responses toward the training. The program demonstrates that ERP Odoo simulation is an effective practice-based learning approach to strengthen students' digital competencies and work readiness in line with industry needs.